2014
DOI: 10.9734/bjpr/2014/7845
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic, Anti-inflammatory and CNS Depressant Activities of the Methanolic Extract of Abelmoschus esculentus Linn. Seed in Mice

Abstract: Aims:The study was carried out to assess the analgesic, anti-inflammatory and CNS depressant activity of the methanolic extract of Abelmoschus esculentus Linn. Seeds. Study Design: The Present study was designed to observe pharmacological activities of the crude extract of the plant Abelmoschus esculentus seeds. The study consisted of hot extraction of the seeds of the A. esculantus with methanol. Afterwards, Methanolic crude extract was filtered and the filtrate was evaporated. Finally, screening of analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Gamma-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system [25]. Earlier investigation has also demonstrated that phenolic acids such as epicatechin were found to be ligands for the GABA A receptors in the central nervous system [26], which led to assumption that they can act as benzodiazepine-like molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system [25]. Earlier investigation has also demonstrated that phenolic acids such as epicatechin were found to be ligands for the GABA A receptors in the central nervous system [26], which led to assumption that they can act as benzodiazepine-like molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Rearing behaviour in mice is regulated by multiple neurotransmitter systems including GABAergic (GABA A ), opioidergic and dopaminergic (D 2 ) systems and receptors [ 36 ]. Locomotor activity in experimental animals are generally reduced by central nervous system (CNS) depressants and increased by CNS stimulants [ 37 , 38 ]. Drug-induced decrease in locomotion of experimental animals may be due to decreased motor effects and/or increased sedation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Group 4 and Group 5 received C. sativum leaves extract at the dose of 100 mg/kg and 200 mg/kg body weight orally, respectively. Group 6 received diclofenac sodium 10 mg/kg body weight orally and served as the standard control [14]. The numbers of contraction of the abdominal muscles together with stretching of hind limbs (writhes) were noted for 30 min, and percent inhibition of writhing was also calculated.…”
Section: Peripheral Analgesic Activitymentioning
confidence: 99%